The Flouting of Conversational Maxims and its Results in New Girl Situational Comedy - Zhafira Ayu Dhamastri (Universitas Gadjah Mada, 2015)
This research aims to identify the types of conversational maxims that are flouted in New Girl situational comedy, study the implied meaning,investigate the most dominant conversational maxim that is being flouted, and identify the results of the flouting. This research took data from the script of New Girl sitcom season 1 episode 1-5. The result of the research shows that all types of conversational maxims, which are maxim of quantity, quality, relation, manner, and the combination of maxims are being flouted by the characters. There are 59 flouted utterances and the most flouted maxim in the situational comedy is the maxim of relation (28,8%). There are 17 types of results of the flouting found: praise, disagreement, suggestion, declaration, agreement, action, enquiry, refusal, order, refusal and request, disagreement and persuasion, declaration and enquiry, suggestion and enquiry, agreement and enquiry, order and declaration, agreement and explanation, and also the combination of agreement, declaration, praise and order.